The Influence of Beauty Standards by Influencers on Student Self-Identity - Lisa Nurul Syifa; Yosi Fransiska Sihotang; Naela Faza Fariha (Feelings: Journal of Counseling and Psychology, 2024)
The current beauty standard has referred to external beauty and no longer relative. Especially current beauty standard just focused on things that are becoming trends.  The amount of impact by influencers can build an opinion and change the mindset of students in social interaction factors. If the influencer thinks that beauty is what is seen physically, over time the student's thinking can be influenced as an influencer thinks. The strong impact of influencers who become role models of beauty standards, many people change their appearance according to beauty standards and lose their identity due to being too carried away by trends in society. This study aims to determine whether the beauty standards provided by influencers have an impact on the self-identity of students of Universitas Mercu Buana Yogyakarta, campus 3, class 2022. The research method used by this study is a quantitative descriptive method, by using statistical tests with the help of the SPSS application. This study obtained the results of the impact of beauty standards by influencers on the self-identity of students of Universitas Mercu Buana Yogyakarta Class of 2022, with a large influence of 29.1% so that other factors as much as 70.9% were influenced by other factors outside the study.